Development Of Business Analysis Learning Model Using The Microsoft Excel Application - Khairunnisa Rangkuti; Mailina Harahap (JASc (Journal of Agribusiness Sciences), 2020)
In the learning process, it is found that there are many students who do not master and understand farming analysis. So that their mastery in responsible for the results of their research when the thesis session on the topic of farming analysis is experiencing many difficulties. The results of research on students' opinions on the problems of learning media and learning implementation show that manual farming calculations are no longer relevant, not interesting and not representative anymore. Utilization of Microsoft Excel program technology produces innovative, professional students so students are able to contribute in the world of work of the industrial revolution 4.0. Stages of farming analysis using Microsoft Excel applications that will be carried out are; 1). Input data from farmers to be analyzed in their farming, 2). Identify and calculate farming costs, namely fixed costs and variable costs, 3). Calculating farm receipts, 4). Calculating farm income, 5). Conduct R / C analysis and B / C, 6). Make interpretations and conclusions from the results of the analysis obtained.